On the equivalence of location choice models : conditional logit, nested logit and poisson - Kurt Schmidheiny; Marius Brülhart (Center for Economic Studies and ifo Institute (CESifo), 2009)
It is well understood that the two most popular empirical models of location choice - conditional logit and Poisson - return identical coefficient estimates when the regressors are not individual specific. We show that these two models differ starkly in terms of their implied predictions. The conditional logit model represents a zero-sum world, in which one region's gain is the other regions' loss. In contrast, the Poisson model implies a positive-sum economy, in which one region's gain is no other region's loss. We also show that all intermediate cases can be represented as a nested logit model with a single outside option. The nested logit turns out to be a linear combination of the conditional logit and Poisson models. Conditional logit and Poisson elasticities mark the polar cases and can therefore serve as boundary values in applied research.
Keywords: C25; R30; H73; 330; firm location; residential choice; conditional logit; nested logit; Poisson count model; Standortwahl; Betriebliche Standortwahl; Wohnstandort; Logit-Modell; Zähldatenmodell; Theorie